GEN Y7, COMPLEMENTAR DE Y1 E Y3 PARA A COLORAÇÃO AMARELO-LARANJA DA SEMENTE DE MILHO - Graner, E. A. (REVISTA DE AGRICULTURA, 2016)
GEN Y7, COMPLEMENTAR DE Y1 E Y3 PARA A COLORAÇÃO AMARELO-LARANJA DA SEMENTE DE MILHO